THE STRATEGIC ROLE OF TRUST IN THE E-TAX SYSTEM TO ENCOURAGE TAX COMPLIANCE AND E-TAX SUSTAINABILITY - Nidya Oktavia Kurniawati; Risma Nurhapsari; Wesly Tumbur Ml Tobing; Novira Indah Prayuni; Paulina Kinanti Eka Praningtyas (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to analyze the influence of business actors' patriotism and tax penalties on e-tax trust, tax compliance, and the sustainability of the e-tax system. Taxes are the backbone of state revenue, but Indonesia's tax ratio is still low. The methodology used is a mixture of qualitative through interviews with at least 10 MSME owners in Central Java and quantitative with Structural Equation Model (SEM) analysis using Partial Least Square (PLS). The results show: tax compliance has a positive and significant effect on e-tax sustainability; trust in e-tax has a negative effect on sustainability and is not significant on compliance; business actors' patriotism has a positive effect on sustainability, compliance, and trust in e-tax; tax penalties have a positive effect on sustainability, a positive but not significant effect on compliance, and a negative effect on trust. Overall, e-tax sustainability is influenced by a combination of compliance, patriotism, trust, and sanctions, with complex dynamics between trust and penalties. These findings emphasize the importance of an integrative strategy that combines regulatory, persuasive, and emotional approaches so that the e-tax system can run effectively, sustainably, and gain public support.